2016
DOI: 10.1007/s11469-016-9710-2
|View full text |Cite
|
Sign up to set email alerts
|

Irish General Practitioner (GP) Perspectives Toward Decriminalisation, Legalisation and Cannabis for Therapeutic Purposes (CTP)

Abstract: Cannabis is the most prevalent illicit drug used globally. Regulatory debate in Ireland on the decriminalisation of cannabis and legalisation for therapeutic purposes (CTP) is on-going. The study aimed to investigate Irish general practitioner (GP) attitudes toward decriminalisation of cannabis and assess levels of support for CTP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…Of the 26 studies included, 13 were conducted in the United States (US),[22, 2528, 30, 33, 37, 38, 4043] four were conducted in Canada,[23, 32, 39, 45] three were conducted in Australia[34–36] and Israel,[21, 31, 46] two were conducted in Ireland,[29, 44] and one covered an international sample. [24] There were 18 studies that sampled medical practitioners,[21, 2426, 2832, 34, 36, 37, 4042, 4446] and three studies that sampled pharmacists. [33, 35, 39] An additional five studies included in this review were grouped according to the high proportion of nursing professionals sampled.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 26 studies included, 13 were conducted in the United States (US),[22, 2528, 30, 33, 37, 38, 4043] four were conducted in Canada,[23, 32, 39, 45] three were conducted in Australia[34–36] and Israel,[21, 31, 46] two were conducted in Ireland,[29, 44] and one covered an international sample. [24] There were 18 studies that sampled medical practitioners,[21, 2426, 2832, 34, 36, 37, 4042, 4446] and three studies that sampled pharmacists. [33, 35, 39] An additional five studies included in this review were grouped according to the high proportion of nursing professionals sampled.…”
Section: Resultsmentioning
confidence: 99%
“…[40] In addition to the support and opposition of medicinal cannabis, three studies reported a high proportion of neutrality when participants were asked whether medicinal cannabis had any clinical utility. [24, 28, 44] Regardless of pre-conceived beliefs; however, the relative support for medicinal cannabis increased if all other treatment options were exhausted or if therapy was to be used in the palliative domain. [26, 28, 29, 36, 37, 40, 41]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional medicine is often seen as the ideal, and physicians argue that medical cannabis fails to comply with the standards of biomedicine. (11,34) They point out the lack of scienti c evidence of safety and e cacy. (11,34) However, some physicians agree on the limited evidence, but argue that other aspects of health care are likewise unsupported by evidence.…”
Section: Attitudes Towards Prescriptionmentioning
confidence: 99%
“…(11,34) They point out the lack of scienti c evidence of safety and e cacy. (11,34) However, some physicians agree on the limited evidence, but argue that other aspects of health care are likewise unsupported by evidence. (11) When physicians consider treatment of pain and palliative care where all conventional methods have been tried, they give much less weight to the lack of evidence and potential harms and are more inclined to support the use of medical cannabis.…”
Section: Attitudes Towards Prescriptionmentioning
confidence: 99%